Harmonizing Success: Elevating Work Culture at PT Oerlikon Balzers Artoda Indonesia through Democratic Leadership and Cultivating an Inspiring Workplace - Tohali Tohali; Agung Surya Dwianto (Jurnal Mirai Management, 2023)
This study aims to determine the impact of the application of democratic leadership style and conducive work environment on work culture at PT Oerlikon Balzers Artoda Indonesia. This research was conducted using a descriptive qualitative approach, with data collected through interviews, observation, and document analysis. The participants of this study were employees of PT Oerlikon Balzers Artoda Indonesia, who were selected using purposive sampling. The results showed that democratic leadership and a conducive work environment affect the work culture at PT Oerlikon Balzers Artoda Indonesia. By implementing democratic leadership and creating a conducive work environment, organisations can create a positive work culture that leads to employee satisfaction, productivity, and retention. Keywords: Work Culture, Democratic Leadership Style, Work Environment